Canalization for colonization: corographic commission and the Panama Canal - Pérez Rancel, Juan José; Universidad Central de Venezuela (Instituto Carlos Arbeláez Camacho para el patrimonio arquitectónico y urbano, 2014)
The Colombian definition of its nationality in the xix century, reached it’s final stage during the explorations organized by the NewGrenade’s Corographic Commission (1850-1858). Along various decades, the need of knowing the size, shape and contentsof the whole virreinato, demanded several studies to solve these incognites. These studies were based more and more withtime in scientifics bases. The Corographic Commission unified the largest volume of data about the natural, material, economiccultural and social realities of the country, and showed its particularities about the other ex colonies independized. Betweenit’s most authentic characteristics the one that highlighted was its geographic condition opened to the globe’s oceans, mostof the scientific studies were directly related with this point, as so many international and commercial activities, territorial occupationplans and other ideas of possibles constructions. The most important of this was the idea of a inter-oceanic canal.Project which the Commission provided with enough time and resources, producing in 1854 the most precise report about thefactibility of constructing the canal and its final route. The role of the Commission Chief, Agustin Codazzi, was determinant forthe definition of the neo-Grenadian territory and in his recommendations about a way between the Caribbean and the Pacific.